Behaviorism, consciousness, and the literary mind - Gang, Joshua, 1981- (Hopkins Studies in Modernism Ser., 2021)
"This book reveals important convergences between modernist writers, experimental psychology, and analytic philosophy of mind-while also providing a new framework for thinking about why language can create the illusion of mental life"--